Effect of audit quality characteristics on client satisfaction of audit firms in Nairobi County - Kamau, J. G. (Strathmore University, 2023)
Providing confidence in the quality of financial reports is a central role of an auditor. To fulfil this purpose, audit quality is key, given the role of financial reports in the financial markets and to the investors. The study aimed to examine the effects of audit quality characteristics on client satisfaction of audit firms in Nairobi County. The study focused more specifically on auditor independence, audit documentation, and code of conduct as audit quality characteristics and their impact on client satisfaction scores as a measure of audit firm performance. Agency and policeman theories formed the theoretical framework upon which the study was based. The study followed positivist research paradigm and quantitative descriptive research design adopted to fulfil this objective. Target population consisted of 600 registered audit firms in Nairobi County. Simple random sampling technique was used to create a sample size of 240 respondents and structured questionnaires used as method of data collection. Out of the 240 respondents, 216 completed and returned questionnaires on time, meaning a minimum requirement of 75% response rate was attained. The collected data were analyzed using quantitative data analysis techniques with the help of the Statistical Package for Social Sciences (SPSS) software. The findings suggest a positive but weak relationship between the variables. However, out of the three variables, the code of ethics has a stronger positive impact on client satisfaction (β = 0.143, t = 1.809, p < 0.05). Audit documentation had a positive impact on audit client satisfaction but the impact was not significant (β = 0.048, t = 0.546, p > 0.05) as well as auditor independence (β = 0.030, t = 0.320, p > 0.05). Therefore, the study concluded that apart from the code of conduct, documentation and independence are not significant predictors of client satisfaction of audit firms in Nairobi County. However, since the research focused only on three attributes, there’s a need for research that looks into other attributes. Also, the study only reveals the extent to which the qualities affect client satisfaction, it does not answer the “how” of the relationship which creates a gap for further research. Key words: Audit quality, Client satisfaction, Audit documentation, Ethical conduct, Audit independence
Full- text thesis